First record of Bemisia tabaci biotype Q in New Zealand - Scott, I.A.W.; Workman, P.J.; Drayton, G.M.; Burnip, G.M. (New Zealand Plant Protection, 2007)
In January 2006 a grower reported failure to control whitefly on greenhouse capsicums in Karaka South Auckland despite high release rates of the biological control agent Encarsia formosa The whitefly was identified morphologically as Bemisia tabaci and capsicum represents a new host record for this species in New Zealand Bemisia tabaci is polyphagous and 24 biotypes are currently recognised worldwide Biotypes B and Q have attracted international attention in the past two decades because of their rapid global spread They are morphologically indistinguishable DNA sequence analyses of samples collected in a survey in 2006 from capsicums and poinsettias revealed the presence of B tabaci biotype Q in New Zealand In a subsequent survey commissioned by Biosecurity New Zealand 12 sites were visited between 27 June and 30 August 2006 Bemisia tabaci was only detected at one site but on multiple hosts Sequences were identical to biotype Q sequences detected during the preliminary survey and to B tabaci biotype Q samples from overseas